2014
DOI: 10.1589/jpts.26.1615
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treatment Table Height on Shoulder Muscles during Ultrasound Therapy Work

Abstract: [Purpose] The purpose of this study was to propose a table height that can reduce shoulder muscle fatigue by analyzing and comparing median frequencies of shoulder muscles at different table heights when performing therapeutic ultrasounds work. [Subjects and Methods] The subjects were 63 healthy male adults who were equally and randomly assigned to a standard height group (SHG), a high height group (HHG), and a low height group (LHG). The standard table height was set at the level of the elbow joint when the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Compared with the usual method of overhead drilling, construction workers’ subjective ratings improved significantly in association with the redesigned tools. C. Y. Kim, Kim, Kang, and Kim (2014) found that a table lower than elbow height can decrease shoulder muscle fatigue in sonographers, even during a work duration of 5 min.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Compared with the usual method of overhead drilling, construction workers’ subjective ratings improved significantly in association with the redesigned tools. C. Y. Kim, Kim, Kang, and Kim (2014) found that a table lower than elbow height can decrease shoulder muscle fatigue in sonographers, even during a work duration of 5 min.…”
Section: Discussionmentioning
confidence: 91%
“…Three studies provided minimal evidence for the fatigue reduction effect of tool redesign. Two high-quality RCTs (C. Y. Kim et al, 2014; Rempel, Star, Barr, Gibbons, & Janowitz, 2009) had positive findings, but one high-quality CCT (Allahyari,, Mortazavi, Khalkhali, & Sanjari, 2016) resulted in no fatigue being detected using EMG and no significant changes in subjective ratings.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation